1996
DOI: 10.1046/j.1365-2125.1996.42615.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CYP3A4, CYP3A5 and CYP3A7 in human duodenal tissue

Abstract: The essential role of cytochrome P450 3A4 (CYP3A4) in human small intestine is well established, and CYP3A5 seems also to be present in most subjects. However, the role of CYP3A7 in the small intestine remains poorly characterized. We have therefore studied the expression of these CYP3A enzymes in the duodenal tissue from 19 patients, using a specific RT‐PCR (reverse transcriptase‐polymerase chain reaction) method. CYP3A4 and CYP3A5 were present at the mRNA level in the duodenum of 18 and 19 of the 19 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 0 publications
1
48
1
1
Order By: Relevance
“…In this study, we found that oral apparent clearance increased but t 1/2 did not change in the CYP3A5 homozygous wild-type group compared with the CYP3A5 homozygous dysfunctional group. Since CYP3A5 is present in the gut (Kivistö et al, 1996) and represents up to more than 50% of total CYP3A content in liver (Kuehl et al, 2001) in individuals who express CYP3A5, we suspect that the reduced maraviroc AUC in the CYP3A5 homozygous wild-type group may be a result of decreased bioavailability due to enhanced CYP3A5-mediated maraviroc oxidative metabolism in the gut and liver of those with this genotype, which was suggested by the lower AUC maraviroc /AUC M1 ratio compared with the homozygous dysfunctional group. The higher AUC maraviroc /AUC M1 ratio in the homozygous dysfunctional group is concordant with our previous in vitro observation that CYP3A5 was the major enzyme responsible for M1 formation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that oral apparent clearance increased but t 1/2 did not change in the CYP3A5 homozygous wild-type group compared with the CYP3A5 homozygous dysfunctional group. Since CYP3A5 is present in the gut (Kivistö et al, 1996) and represents up to more than 50% of total CYP3A content in liver (Kuehl et al, 2001) in individuals who express CYP3A5, we suspect that the reduced maraviroc AUC in the CYP3A5 homozygous wild-type group may be a result of decreased bioavailability due to enhanced CYP3A5-mediated maraviroc oxidative metabolism in the gut and liver of those with this genotype, which was suggested by the lower AUC maraviroc /AUC M1 ratio compared with the homozygous dysfunctional group. The higher AUC maraviroc /AUC M1 ratio in the homozygous dysfunctional group is concordant with our previous in vitro observation that CYP3A5 was the major enzyme responsible for M1 formation.…”
Section: Discussionmentioning
confidence: 99%
“…All these findings suggested that GLS4 was a sensitive substrate of CYP3A, and first-pass metabolism played an important role in GLS4 elimination. Although the function of the gut wall in the presystemic metabolism of GLS4 is unknown, the interactions between GLS4 and CYP3A modulators possibly occur in the duodenal wall, as shown by the extensive expression of CYP3A in the duodenal wall [24] and more significant effects on C max and AUC of GLS4 than T 1/2 .…”
Section: Discussionmentioning
confidence: 99%
“…This is of considerable interest since hepatic CYP3A5 is expressed in an appreciable amount in only 25% of the population and then could actively participate to the overall metabolism of amprenavir. Furthermore, CYP3A5 is also expressed in a non-negligible amount in the intestine and could increase the elimination of amprenavir (Kivisto et al, 1996). CYP3A7, the third member of the CYP3A subfamily had virtually no activity.…”
Section: Discussionmentioning
confidence: 99%